2016
DOI: 10.1063/1.4945412
|View full text |Cite
|
Sign up to set email alerts
|

On-chip pressure sensor using single-layer concentric chambers

Abstract: A vision-based on-chip sensor for sensing local pressure inside a microfluidic device is proposed and evaluated in this paper. The local pressure is determined from the change of color intensity in the sensing chamber which is pre-filled with colored fluid. The working principle of the sensor is based on polydimethylsiloxane deformation. The pressure at the point of interest is guided into a deformation chamber, where the structural stiffness is softened by chamber geometry, and thus, the chamber deforms as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Third, pressure sensors can also be used for implantable pressure monitoring, such as blood, intraocular, and intracranial pressures [ 23 , 24 ]. However, due to the limited range of microchannel dimensions, it is very difficult to integrate an additional pressure-sensing functionality without disturbing the flow field [ 25 , 26 , 27 ]. Therefore, measuring pressure inside microchannels is challenging and novel methods are demanded [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, pressure sensors can also be used for implantable pressure monitoring, such as blood, intraocular, and intracranial pressures [ 23 , 24 ]. However, due to the limited range of microchannel dimensions, it is very difficult to integrate an additional pressure-sensing functionality without disturbing the flow field [ 25 , 26 , 27 ]. Therefore, measuring pressure inside microchannels is challenging and novel methods are demanded [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed in the literature for pressure measurement inside microchannels [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The majority of these published approaches are mechanical in nature and primarily use a membrane that deflects as a function of the applied pressure [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common pressure sensors used in microfluidics are capacitive [17] and piezoresistive [18,19,20]. Besides these, other variations, such as optical [21,22,23], vision-based [24] and resonant sensors, do exist. A general review of several pressure-sensing technologies for microdevices can be found in Eaton and Smith [25].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are many examples of the integration of a number of different types of pressure sensors with PDMS [7][8][9][10][11][12][13][14][15][16]. In these cases the reported pressure sensors have been custom made and involve multi-step microsystem fabrication processes, adding an element of considerable complexity.…”
Section: Introductionmentioning
confidence: 99%
“…This paper demonstrates that commercial pressure sensors can monitor the subtle pressure changes associated with the individual features of two important boiling modes and is suitable for characterising boiling in microchannels. This approach can also be adapted to address other applications for which bespoke sensors have been developed; i.e cell-culture [8], DNA and cell biology studies [15], chemical mixing, reaction, extraction, separation [10], characterisation of industrial fluids such as lubricants and coatings [14] and particle sorting and separation [16].…”
Section: Introductionmentioning
confidence: 99%